ANALISIS KONFLIK PEMEKARAN BANJAR ADAT KUBU DAN BANJAR ADAT GRAHA CANTHI KARANGASEM - Bulan, Susandra Yunitha; Noak, Piers Andreas; Pramana, Gede Indra (Jurnal Nawala Politika; Vol 1 No 1 (2022): Jurnal Ilmu Politik 2022, 2022)
This study aims to analyze the conflict and analyze the factors causing the conflict of division between the Banjar Adat Kubu and the Banjar Adat Graha Canthi Karagasem. The surgical instrument used in this study is the conflict stage theory proposed by Simon Fisher. The stages of conflict are used to find out how the escalation of the conflict took place and what were the factors causing the division conflict in the Banjar adat Kubu and Banjar Adat Graha Canthi. This research uses qualitative methods through interviews, field observations and documentation. The theory of conflict stages consists of the pre-conflict stage, the confrontation stage, the crisis stage, the effect stage and the post-conflict stage. Through the stages of conflict, the researchers found several factors that caused the division conflict in the Kubu Banjar adat and the Graha Canthi adat Banjar including structural factors, interest factors, human relations factors, and finally the data factor.